(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article explores the evolution of the campus novel genre in the works of British novelist and academic David Lodge. It focuses on his Campus Trilogy—Changing Places (1975), Small World (1984), and Nice Work (1988)—tracing how Lodge blends satire, cultural critique, and literary theory to both entertain and interrogate the academic world. Lodge’s fiction mirrors transformations in academia from the 1970s to the 1990s, including globalization, theory-driven scholarship, and the increasing intersection between universities and external socio-economic forces. His contribution reshaped the campus novel, elevating it beyond parody into a serious literary form.